Depressive Disorder With Panic Attacks After Replacement of an Intrauterine Device Containing Levonorgestrel: A Case Report - Zeiss, René; Schönfeldt-Lecuona, Carlos; Gahr, Maximilian; Graf, Heiko (Frontiers in Psychiatry, 2020)
The levonorgestrel-releasing intrauterine system (LNG-IUS) is used as hormonal contraception by millions of women worldwide. It is considered as a safe device with low rates of systemic adverse drug reactions (ADRs). However, an emerging evidence suggest mood changes as ADRs. Whereas most of these studies report psychiatric ADRs after the first implantation of the LNG-IUS, it has to be considered that these may also occur after replacement, even when psychiatric symptoms were not evident at the time of the initial insertion. A potential explanation for the development of psychiatric ADRs in subsequent LNG-IUS may rely on fluctuations of sex hormones throughout the female life cycle with changing windows of vulnerabilities for developing mood disorders. Thus, the reliable contraception for women remain a continual challenge. We present the case of a 41-year-old woman that used the LNG-IUS (Mirena®) for contraception over 5 years without any complaints. Within the first weeks after insertion of the second LNG-IUS, she developed a depressive syndrome and anxieties. An extensive somatic, including gynecological examination revealed no pathological findings and a mental disorder was suggested. Due to the patient´s request and the recommendation of her psychiatrist, the device was removed and led to a remission of her mental complaints up to a 6- and 12-months follow-up. Beyond the mood changes considerably affecting her quality of life, the patient raised the concerns that she has never been informed about potential ADRs on mental health and her remarks regarding the potential association between psychiatric symptoms and the LNG-IUS were considered as groundless. With this case, we strengthen previous observations regarding mood changes under LNG-IUS. Moreover, we illustrate that psychiatric symptoms may also occur as ADRs during the subsequent insertion. Thus, we emphasize that psychiatric symptoms have to be clearly communicated as ADRs to patients with LNG-IUS within a written informed consent and should be routinely examined by gynecologists.